Organizations analysis with complex network theory - Banova, Todorka; Mishkovski, Igor; Trajanov, Dimitar; Kocarev, Ljupcho (Springer, Berlin, Heidelberg, 2010)
In this paper, we propose network measures and analytical procedures for modeling the structure and the behavior of the basic types of organizations, such as: line, functional, line-and-staff, project and matrix organization. In order to obtain some tangible information about the connectivity between employees and structural properties of organizations, we develop network generators for all five types of organizations. We review various roles and groups of employees within the organizational network, and we assess social position and impact of a particular employee. Except, assessed locations of actors within an organizational network, we analyze the structure of network to find specific employees who have similar roles in the organization and have a tendency to be equivalent in terms of their potential to act in the organization. We estimate what is the confidentiality of the organizational network depending on the removal of a certain communication between employees and what is the percentage of communications that disconnect the organization in unconnected parts.
Keywords: Organization, complex networks, organizational network models, measurements, organizational network analysis